Influence of Statin Therapy on the Incidence of Cardiovascular Events, Cancer, and All-Cause Mortality in People Living With HIV: A Meta-Analysis - Li, Yanping; Wang, Zhandi; Xia, Haimei; Zhang, Ju (Frontiers in Medicine, 2021)
Background: Possible influences of statin therapy on the risk of cardiovascular events, cancer, and all-cause mortality in people living with HIV (PLWH) remain unclear. We performed a meta-analysis to systematically evaluate the efficacy of statin in PLWH. Methods: Relevant cohort studies were retrieved via search of Medline, Embase, and Web of Science databases until June 14, 2021. The data was combined with a random-effect model by incorporating the between-study heterogeneity. Results: Twelve multivariate cohort studies with 162252 participants were eligible for the meta-analysis, 36253 (22.3%) of them were statin users. Pooled results showed that statin use was independently related to a reduced mortality risk in PLWH (adjusted risk ratio [RR]: 0.56, 95% confidence interval: 0.44 to 0.72, P < 0.001, I2 = 41%). In addition, results of meta-analysis showed that statin use was not significantly associated with a reduced risk of cardiovascular events in PLWH as compared to statin non-users (RR: 1.14, 95% CI: 0.80 to 1.63, P = 0.48, I2 = 42%). However, statin use was significantly related to a reduced risk of cancer in PLWH (RR: 0.73, 95% CI: 0.58 to 0.93, P = 0.009, I2 = 49%). Sensitivity analyses by excluding one study at a time showed consistent results. No significant publication biases were observed. Conclusions: Statin use is associated with reduced all-cause mortality in PLWH. In addition, statin use is related to a reduced risk of cancer, although the risk of cardiovascular events seems not significantly affected.